ANALISIS SISTEM PENDINGIN KAPAL IKAN BERBASIS KARBON DIOKSIDA (R-744) DENGAN ENGINEERING EQUATION SOLVER - Dea Zulpiana Putri, (2024)
Indonesian fishermen are still left behind, one of which is about the need for effective fish cooling storage facilities to keep the catches cool during storage, where fishing vessels in Indonesia still use conventional refrigerant, namely R-134a which damages ozone and climate. But in Europe it has used carbon dioxide (R-744) which has a lot of better renewal for nature. This study aims to compare and analyse enthalpy, energy and Coefficient Of Performance (COP) in fish boat cooling systems with variations in pressure and temperature, with temperatures in Indonesia, as well as designing a refrigerant engine scheme. In this study, do a thermodynamic simulation using the Engineering Equation Solver software where the pressure is varied from 800 [Kpa] to 1000 [Kpa] and the temperature is varied to low and high temperature, for low temperature from -2C to -6C and high temperature from 31C to 40C. The results of this simulation have shown that the results of the COP against the lowest pressure R-744 with a value of 1.4 [-] while the temperature show the results of 4[-], so it was found that the COP R-744 that is varied against the pressure is better in performance than the variation in temperature. Thus this research can provide further development regarding carbon dioxide (R-744) for fishermen in Indonesia. Keywords: Refrigerant, R-744, Fishing Vessel.